Labile Dissolved Organic Matter Compound Characteristics Select for Divergence in Marine Bacterial Activity and Transcription - Pontiller, Benjamin; Martínez-García, Sandra; Lundin, Daniel; Pinhassi, Jarone (Frontiers in Microbiology, 2020)
Bacteria play a key role in the oceanic carbon cycle partly because they rapidly assimilate labile dissolved organic matter (DOM). However, knowledge of the molecular mechanisms at work when bacterioplankton metabolize DOM is still limited. We conducted seawater culture enrichment experiments with ecologically relevant DOM polymer and monomer model compounds for the compound classes carbohydrates (polysaccharides versus monosaccharides), proteins (polypeptides versus amino acids) and nucleic acids (DNA versus nucleotides). We noted pronounced changes in bacterial growth, activity, and transcription related to DOM characteristics. Transcriptional responses differed between compound classes, showing “core gene” responses for carbohydrates (notably genes for labile carbon compound utilization, glucosidases, and motility and chemotaxis), proteins (e.g. amino acids and phosphorus metabolism genes), and nucleic acids (e.g. DNA conversion, nucleotides utilization, and TonB transporters). Moreover, there was a strong divergence in functional transcription at the level of particular monomers and polymers mediated by distinct bacterial taxa primarily in the carbohydrates and protein compound classes. These specific responses included membrane transporters (Oceanospirillales; in monosaccharides treatment), motility and glycogen utilization (Alteromonadales; in polysaccharides), uptake systems for amino acids and polyamines (Pseudomonadales; in amino acids), and transferases and uptake systems (Flavobacteriales; in polypeptides). Responses specific to DNA and nucleotides were limited both dominated by Alteromonadales. Altogether, our findings show that two important facets of DOM, compound class and condensation state, shape bacterial gene expression, and ultimately select for distinct bacterial (functional) groups. These findings emphasize the interdependency of marine bacteria and labile dissolved organic matter for regulating the transformation of DOM in surface waters and thereby determining the central role bacteria play in the planetary carbon cycle.